Analisis Kebutuhan Bahan Ajar Biologi PBL-SSI terintegrasi Ayat Al-Qur’an se-SMA Muhammadiyah di Palembang - Septi Meliani Hartato; Wulandari Saputri (Departement of Mathematics Education, 2024)
This study aims to analyze the needs for biology teaching materials based on the PBL model with SSI content integrated with the Al-Qur'an to enhance the critical thinking and collaboration skills of Muhammadiyah High School students in Palembang. The research was conducted using a descriptive method in January 2023 in Palembang, with data collection techniques including questionnaires, interviews, and documentation. The results of the study indicate that: (1) the implementation of the learning model has not reached an optimal level, (2) the teaching materials used have not been integrated with PBL, SSI, and/or Quranic verses, resulting in a lack of training in students' critical thinking and collaboration skills, as well as a lack of utilization of digital technology in learning, (3) the integration of Quranic verses with material and community cases is still not optimal, (4) students and teachers consider the human regulatory system material to be the most difficult, with a percentage of 68.8% for students and 75% for teachers, (5) teachers (100%) and students (92.2%) hope for the creation of PBL-SSI integrated e-magazine teaching materials with Quranic verses to enhance students' critical thinking and collaboration skills in the human regulatory system material.